2016
DOI: 10.1002/jmv.24667
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression profiles in patients with acute Crimean Congo hemorrhagic fever reveal possible adjustments to cellular pathways

Abstract: Several viral diseases are associated with altered microRNA (miRNA) expression, which can provide vital information about how cellular pathways respond to infection. However, the miRNA profile of Crimean Congo Hemorrhagic Fever (CCHFV) infections are not known. To address this gap, we performed real-time PCR-based miRNA analysis in individuals with acute Crimean Congo Hemorrhagic Fever (CCHFV) infections, with the goal of identifying pathways that might be associated with this disease. Peripheral blood mononuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
0
11
0
2
Order By: Relevance
“…Through a combination of bioinformatics and gene profiling we were able to identify host pathways associated with CCHFV pathogenesis in liver cell lines. While several groups have identified genes with altered expression in CCHFV infection [43][44][45], to our knowledge this is the first time next-generation sequencing has been applied to examine the host-response in vitro to CCHFV. Our data indicates that CCHFV infection of hepatocyte cell lines induced robust antiviral and pro-inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Through a combination of bioinformatics and gene profiling we were able to identify host pathways associated with CCHFV pathogenesis in liver cell lines. While several groups have identified genes with altered expression in CCHFV infection [43][44][45], to our knowledge this is the first time next-generation sequencing has been applied to examine the host-response in vitro to CCHFV. Our data indicates that CCHFV infection of hepatocyte cell lines induced robust antiviral and pro-inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary analysis showed that the expression of microRNAs related to regulation of cytokine expression is altered in CCHF patients (Demir et al, 2017). Genetic factors and immune status of the host, as well as genetic differences in CCHFV strains, may play a significant role in the virus-host interface, however, there are no studies available.…”
Section: Host-pathogen Interactionsmentioning
confidence: 99%
“…Increased expression of SPRED1 was suggested to be one of the mechanisms that augment endothelial cells permeability, leading to HPS. A recent study with PBMC of patients presenting acute hemorrhagic fever caused by the Crimean-Congo Hemorrhagic Fever Virus (CCHFV) showed the deregulation of several miRNAs, some of them associated with innate immunity and viral escape mechanisms [ 48 ]. The only study with phleboviruses described the association between miR-142-3p and the endocytic vesicle protein VAMP3, suggesting a control mechanism for the intracellular trafficking of Uukuniemi Virus (UUKV) [ 49 ].…”
Section: Introductionmentioning
confidence: 99%